Analisis Parasetamol Tablet dengan Metode Fourier Transform Infra Red (FTIR) - Safitri Saragih; Suprianto Suprianto; Samran Samran (Yayasan Penelitian dan Inovasi Sumatera, 2024)
Background: Paracetamol, a widely used analgesic and antipyretic medication, is commonly prescribed in government healthcare facilities. The FTIR method provides rapid measurements by analyzing spectral graphs that reveal the functional groups within the tested compounds. According to the Indonesian Pharmacopoeia, VI Edition 2020, paracetamol content in tablet formulations must range between 90.0% and 110.0%. Objective: This study aimed to evaluate the paracetamol content in tablet preparations and assess their compliance with the 2020 Indonesian Pharmacopoeia standards and the packaging labels. Method: The research was conducted experimentally using FTIR spectroscopy. A solvent mixture of ethanol and distilled water (1:1) was employed, with analyses performed over the wavelength range of 4000–400 cm⁻¹. Results: The paracetamol content was found to be highest in tablet B (100.33 ± 1.003%), followed by tablet A (100.29 ± 1.002%), tablet D (100.24 ± 1.002%), and tablet E (100.14 ± 1.001%), with the lowest levels observed in tablet C (99.69 ± 0.996%). Method validation indicated an RSD value of 0.056%, confirming that the procedure was accurate and reliable. Conclusion: The findings demonstrate that the FTIR method is suitable for the quantitative analysis of paracetamol in tablet formulations. Moreover, the results meet the standards outlined in the 2020 VI Edition of the Indonesian Pharmacopoeia.